BIOACTIVE METABOLITES OF Lactiplantibacillus plantarum ISOLATED FROM Sonchus arvensis AS AN ANTIMICROBIAL AGENT - Syaputri, Yolani; Nurhidayat, Fahmi; Wulandari, Indri; Rahayu, Sri Rejeki (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Sonchus arvensis is a plant widely found in Southeast Asia and often used in traditional medicine. Lactiplantibacillus plantarum is a bacteria isolated from S. arvensis and categorized as qualified presumption of safety by the European Food Safety Authority and the US Food and Drug Administration. Therefore, this study aimed to determine the bioactive metabolites of Lpb. plantarum as antimicrobial agents. Lactic acid bacteria (LAB) were isolated using the serial dilution method, followed by isolation and amplification of the DNA through a 16S rRNA universal primer. Antimicrobial activity was screened using the well-diffusion method. Plantaricin gene identification was performed using PCR and the determination of lactic acid content was conducted using Spectrophotometric. In addition, the titration method was used to measure and determine the hydrogen peroxide. The results showed that Lpb. plantarum had higher inhibition toward pathogen bacteria than Lc. lactis. Lpb. plantarum had the largest inhibition zone against B. subtillis, followed by S. aureus and E. coli, respectively. It was discovered that Lpb. plantarum precipitated with ammonium sulfate had a greater protein content and antibacterial activity. Furthermore, Lpb. plantarum, which encodes plnA and plnEF, produced lactic acid and hydrogen peroxide at concentrations of 3.0158±0.2774 mg/mL and 0.195±0.04 mg/mL, respectively.